Preconception care services in Northern Ethiopia: A qualitative exploration of awareness, experiences, challenges, opportunities, and prospects - Gebremedhin Gebreegziabher Gebretsadik; Alemayehu Bayray Kahsay; Andargachew Kassa Biratu; Amanuel Gessessew; Zohra S. Lassi; Afework Mulugeta (PLoS ONE, 2025)
Introduction Preconception care (PCC) has emerged as a key component of the maternal continuum of care worldwide, focusing on reducing poor pregnancy outcomes. Improving services requires addressing opportunities and challenges within the health system, but in Ethiopia, it is often neglected. Hence, this study explores the awareness, experiences, challenges, and opportunities related to PCC services in Tigray, Northern Ethiopia. Methods We conducted an exploratory qualitative study involving 21 in-depth interviews with mothers who experienced adverse pregnancy outcomes and health care providers (HCPs), who work in maternal, neonatal, and child health, and health extension workers. Additionally, we held six focus group discussions with women with a history of pregnancy. We also conducted key informant interviews with 10 maternal, newborn and child health experts from the regional health bureau, district health offices, and professional associations. The study was conducted from January 26, 2024, to April 4, 2024, across four rural districts and two urban areas in Tigray, Northern Ethiopia. Discussions and interviews were audio-recorded, transcribed into the local language “Tigrigna”, then translated into English and thematically coded using ATLAS-ti v.7.5.4 software. Results Some women, particularly those belonging to high-risk groups, are aware of PCC services. Majority of HCPs, especially gynecologists and physicians, have some knowledge of PCC, recognize its importance, and provide specific components of PCC interventions. However, these services are often delivered in a fragmented manner, primarily targeting high-risk women. Identified challenges include traditional beliefs and misconceptions, insufficient counseling on contraceptive services, social influences, service costs, high workloads, lack of medicines and medical equipment, and the fragment-based services . Conversely, opportunities include utilizing existing community platforms and an expressed desire for PCC services. Moreover, diverse communication strategies, linking communities with health facilities, involving high-risk mothers as educational role models, and integrating package-based PCC services into the healthcare system were explored as perceived suggestions. Conclusion Apart from high-risk women, most women have little to no awareness about PCC services. Furthermore, although many HCPs possess some understanding of PCC, they deliver only a limited range of interventions, primarily catering to self-initiated high-risk mothers. Challenges identified include traditional beliefs and misconceptions, inadequate counseling on contraceptive services, social influences, high service costs, and fragmented service delivery. Existing community platforms and the perceived desire for PCC services were highlighted as opportunities to enhance PCC services. Strategies such as utilizing diverse communication methods, involving high-risk mothers as role models, strengthening community engagement activities, and improving linkages between communities and health facilities were proposed. Additionally, promoting home-based self-care was explored as a suggestion for improving PCC services. Integrating package-based PCC services into the healthcare system to routinely serve all eligible women of reproductive age was recommended to improve both awareness and uptake of PCC. Finally, tailored interventions were deemed essential for improving PCC awareness and utilization both at the community and facility levels.